Adrenocorticotropic hormone at pathophysiological concentration modulates the proliferation and differentiation of bone cells - Tsuyoshi Sato; Yoshie Sano; Masahiro Niimura; Shoichiro Kokabu; Michihiko Usui; Tetsuya Yoda (Elsevier, 2015)
Background/purpose: Adrenocorticotropic hormone (ACTH) plays a vital role in maintaining the function of the hypothalamic-pituitary-adrenal axis. Recent studies have demonstrated that ACTH directly affects the proliferation and differentiation of bone cells. However, the ACTH concentrations used in these studies appear to be markedly higher than the physiological concentrations. Here, we investigated whether ACTH at pathophysiological concentration affects the proliferation and differentiation of osteoblasts and osteoclasts. Materials and methods: We evaluated the effect of ACTH at pathophysiological concentration on osteoclasts using tartrate-resistant acid phosphatase staining and on osteoblasts using alkaline phosphatase activity assay. Additionally, we conducted reverse transcriptase-polymerase chain reaction analysis. Results: We found that at pathophysiological concentration, ACTH does not affect osteoblast proliferation and inhibits osteoblast differentiation. Moreover, we showed that at pathophysiological concentration, ACTH does not affect the proliferation of bone marrow macrophages, but promotes differentiation of osteoclasts and induces expression of genes involved in bone resorption. Conclusion: Taken together, our findings suggest that ACTH modulates the proliferation and differentiation of bone cells in vitro at pathophysiological concentration.